A policy and research agenda for Asia's poultry industry - Sango Mahanty; Assa Doron; Rebecca Hamilton (Asia & the Pacific Policy Studies, 2023)
Abstract Meat consumption and production in Asia have boomed over the last decade to meet growing regional and global demand. Asia now supplies around 40% of the global broiler or meat chicken industry. Dominant policy frameworks such as ‘One Health’ aim to manage the health risks associated with factory livestock farming, which has rightly become a major concern because of regular disease outbreaks. Yet this approach provides a limited basis for addressing broader risks and challenges associated with what we term the Asian ‘broiler complex’. This includes the intertwined networks of feed production, factory farming and meat distribution nodes through which health and environmental risks can accumulate and be amplified. By applying this broader lens, we highlight the need to better understand the industry's pressing environmental, animal welfare, social and health challenges to inform more integrated policy approaches.